The National and Regional Prevalence Rates of Disability, Type, of Disability and Severity in Saudi Arabia—Analysis of 2016 Demographic Survey Data - Bindawas, Saad M. (Int J Environ Res Public Health, 2018)
The prevalence of disability varies between countries ranging from less than 1% to up to 30% in some countries, thus, the estimated global disability prevalence is about 15%. However, it is unknown what the current estimate of disability and its types and severity are in Saudi Arabia. Thus, the objective of this study is to estimate national and regional prevalence rates of any disability, types of disability, and their severity among Saudi populations. Data on disability status were extracted from the national demographic survey conducted in 2016 as reported by the General Authority for Statistics, Saudi Arabia (N = 20,064,970). Prevalence rates per a population of 100,000 of any disability, type of disability, and its severity were calculated at the national level and in all 13 regions. Out of 20,064,970 Saudi citizens surveyed, 667,280 citizens reported disabilities, accounting for a prevalence rate of 3326 per a population of 100,000 (3.3%). Individuals aged 60 years and above (11,014) and males (3818) had a higher prevalence rate of disability compared with females (2813). The Tabuk region has the highest rate of reported disability, at 4.3%. The prevalence rates of extreme disabilities in mobility and sight were higher in Madinah (57,343) and Northern border (41,236) regions, respectively. In Saudi Arabia, more than half a million Saudi citizens (1 out of every 30 individuals) reported the presence of disability during the year 2016. A higher prevalence rate of disability was seen among those aged 60 years and above, and males. Targeted efforts are required at the national and regional levels to expand and improve rehabilitation and social services for all people with disabilities.